2023
DOI: 10.1177/19458924231153485
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction Now and in the Future in CRSwNP

Abstract: Background Chronic rhinosinusitis (CRS) is the leading cause of olfactory dysfunction in the general population. Olfactory dysfunction is more common in patients with CRS with nasal polyposis (CRSwNP) compared to those without polyps. Purpose The present review aims to summarize the current literature on the mechanism behind olfactory dysfunction in CRSwNP and the impact of therapy on olfactory outcomes in this patient population. Methods A comprehensive review of the available literature on olfaction in CRSwN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…It is interesting to note that we did not observe a reduction of olfactory function in several other conditions that are typically thought to be associated with a reduction of olfactory function. This includes a history of surgery for nasal polyposis ( Qureshi and Lane 2023 ), kidney disease including kidney failure ( Frasnelli et al 2002 ), diabetes ( Faour et al 2022 ), epilepsy ( Khurshid et al 2019 ), and migraine ( Kandemir et al 2022 ). Similarly, self-reported exposure to a variety of relatively common potential toxins such as detergents, exhausts, wood dust, pesticides, and others was also not associated with a reduction of odor identification abilities.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that we did not observe a reduction of olfactory function in several other conditions that are typically thought to be associated with a reduction of olfactory function. This includes a history of surgery for nasal polyposis ( Qureshi and Lane 2023 ), kidney disease including kidney failure ( Frasnelli et al 2002 ), diabetes ( Faour et al 2022 ), epilepsy ( Khurshid et al 2019 ), and migraine ( Kandemir et al 2022 ). Similarly, self-reported exposure to a variety of relatively common potential toxins such as detergents, exhausts, wood dust, pesticides, and others was also not associated with a reduction of odor identification abilities.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of OD in patients with CRS is not completely understood. While it has been hypothesized that OD results from airflow obstruction often secondary to polyps [ 21 , 22 ], studies have shown residual OD in some individuals even with medical and surgical treatments to reduce or remove polyps [ 22 , 23 ]. It has also been hypothesized that OC inflammation may impair signaling between olfactory receptors and the olfactory cortex [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…While it has been hypothesized that OD results from airflow obstruction often secondary to polyps [ 21 , 22 ], studies have shown residual OD in some individuals even with medical and surgical treatments to reduce or remove polyps [ 22 , 23 ]. It has also been hypothesized that OC inflammation may impair signaling between olfactory receptors and the olfactory cortex [ 21 , 22 ]. As future studies investigate and provide a better understanding of the pathophysiology of OD in CRS, novel treatments that need to be delivered to the OC to improve olfactory function will likely be developed.…”
Section: Discussionmentioning
confidence: 99%